Modeling of Nanocomposite Structures to Evaluate the Effect of Nanoplatelet Interphase Region on Electric Field Intensity - Sharip, M.R.M.; Lau, K.Y.; Zaidel, D.N.A. (UTEM, 2017)
The effects of the nanoplatelet interphase region on the electric field intensity within a nanocomposite structures are presented in this paper. The modeling of the nanoplatelet and its interphases was performed by using the Finite Element Method Magnetics (FEMM) 4.2 software. Two possible structures of the nanoplatelet were simulated – with and without interphases. In addition, two different models of interphase structures surrounding the nanoplatelet were analyzed – one with rectangular-shaped interphase and the other with circularly-shaped interphase. Both sets of the model interphase were assumed to have different thicknesses and radii. The results showed that the presence of the nanoplatelet interphase affected the electric field intensity of the nanocomposite.